Graphene based self-healing materials. (May 2019) - Li, Guanghao; Xiao, Peishuang; Hou, Shengyue; Huang, Yi
Abstract: Self-healing materials are one kind of intelligent material capable of feeling external stimulus to repair themselves after damage and restore their intrinsic properties, thus can extend lifespan, improve security, save cost, and achieve sustainable development. However, their mechanical property, energy absorption and conversion efficiency, and self-healing property still need to be further enhanced in scientific research and practical application. Graphene is a two-dimensional material with outstanding mechanical, electrical, and thermal properties, as well as excellent energy absorption and conversion characteristics. Therefore, numerous attempts, focused on the research of graphene based self-healing materials, are being raised every year. In this brief review, graphene based self-healing materials are summarized according to their synthesis methods, self-healing pathways, and applications in different fields. Eventually, a brief summary, the challenges and future prospect are highlighted. Graphical abstract: Self-healing materials are one kind of intelligent material capable of feeling external stimulus to repair themselves after damage and restore their intrinsic properties, thus can extend lifespan, improve security, save cost, and achieve sustainable development. In this review, graphene based self-healing materials are summarized according to their synthesis methods, self-healing pathways, and applications in different fields. Eventually, a brief summary, the challenges and future prospect are highlighted. Image 101453